2009
DOI: 10.1245/s10434-009-0483-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Factors Related to 18F-FDG-PET Positivity in the Diagnosis of Recurrence and/or Metastasis in Patients with Differentiated Thyroid Cancer

Abstract: (18)F-FDG-PET study offers a high sensitivity and positive predictive value (PPV) in patients with negative WBS and Tg positive. The use of FDG-PET is strongly recommended in DTC patients with large tumors, thyroid capsule invasion or poor-prognosis variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 33 publications
2
22
0
1
Order By: Relevance
“…In the presence of low Tg levels, FDG-PET had an NPV of 93% [48]. Similarly, Esteva et al [49] reported FDG-PET findings in 50 patients with an elevated Tg level and a negative WBS and found that FDG-PET was positive in 32 of 39 (82.1%) patients with confirmed recurrence and negative in seven of 11 (63.6%) patients with no confirmed recurrence. The sensitivity and specificity were 82% and 64%, respectively.…”
Section: Role Of Fdg-pet In Patients With Dtc Recurrencementioning
confidence: 85%
See 1 more Smart Citation
“…In the presence of low Tg levels, FDG-PET had an NPV of 93% [48]. Similarly, Esteva et al [49] reported FDG-PET findings in 50 patients with an elevated Tg level and a negative WBS and found that FDG-PET was positive in 32 of 39 (82.1%) patients with confirmed recurrence and negative in seven of 11 (63.6%) patients with no confirmed recurrence. The sensitivity and specificity were 82% and 64%, respectively.…”
Section: Role Of Fdg-pet In Patients With Dtc Recurrencementioning
confidence: 85%
“…Tumor size and capsular tumor invasion were factors significantly associated with a positive FDG-PET study. They also concluded that FDG-PET is an extremely useful imaging tool in patients with a negative WBS and raised Tg level [49]. The SUV max reported in patients with recurrent Hürthle cell carcinoma was remarkable.…”
Section: Role Of Fdg-pet In Patients With Dtc Recurrencementioning
confidence: 93%
“…According to the present results, vascular invasion and metastatic and lymphatic spread are all correlated with positive results on 18F-FDG PET/CT. Capsule invasion [24] or vascular invasion [25] are negative prognostic factors in DTC and positively correlate with positive 18F-FDG-PET results. Other authors [26] concluded that PET positivity correlates with extrathyroidal spread and elevated Tg in recurrent/metastatic DTC.…”
Section: Discussionmentioning
confidence: 96%
“…In children, the neck and chest are the most likely sites of persistent disease, and contrast-enhanced imaging of these areas with CT or MRI is favored when US cannot identify disease. 18 FDG-PET/CT has become a commonly used tool in the evaluation of adults with persistent non-iodine-avid thyroid cancer (3,(321)(322)(323)(324)(325)(326) and appears to offer prognostic information that might change clinical management (327)(328)(329)(330). However, there are extremely limited data regarding the use of 18 FDG-PET/CT in children except for a case report (331), isolated pediatric subjects embedded within adult studies, and unpublished data that suggest low sensitivity of 18 FDG-PET/CT to identify residual disease in children that otherwise cannot be identified via cervical US and crosssectional imaging of the neck and chest (personal communication, SGW).…”
Section: Recommendation Rating: C and Recommendation 25(b)mentioning
confidence: 99%